Biomaterial-based strategy for bone tumor therapy and bone defect regeneration: An innovative application option - Zhang, Yue; Wu, Yunjiao; Qiao, Xinyi; Lin, Tie; Wang, Yicun; Wang, Meng (Frontiers in Materials, 2022)
Bone tumors are deadly and incurable diseases that invade large areas of bone, resulting in bone defects. Traditional therapies combining surgery, chemotherapy, and radiation have reached their limit of efficacy, motivating efforts to develop new therapeutic methods. Fortunately, the development of biomaterials provides innovative options for bone tumor treatment. Suitable biomaterials are capable of simultaneously providing tumor therapy and promoting bone regeneration. This review summarizes recent progress in the effort to achieve new strategies for bone tumor treatment using biomaterials, focusing on the innovative scaffold design. It also discusses the development of nanocarrier-based drug delivery systems and hyperthermia therapy for bone tumor treatment. In the future, biomaterial-based strategies are likely to become the most effective and reliable options for treating bone tumors, and they have the potential to greatly improve the prognosis and quality of life for patients.